A CROSS-SECTIONAL STUDY TO EVALUATE PRESCRIPTION-TO- ADMINISTRATION TIME IN PATIENTS PRESENTING WITH PAIN IN EMERGENCY DEPARTMENT OF A TERTIARY CARE HOSPITAL OF PAKISTAN (The Research of Medical Science Review, 2025)
Introduction: Pain, irrespective of its etiology, is one of the most prevalent complaints prompting patients to seek care in the emergency department (ED). The prompt administration of analgesics alleviates discomfort, provides reassurance, and facilitates early and comprehensive clinical evaluation. Notwithstanding its significance, timely and efficient pain management is frequently neglected in acute care environments owing to various systemic and operational obstacles. Extended delays in obtaining analgesics, particularly in crowded emergency departments, have been associated with adverse physical and psychological consequences. Objective: This study aims to evaluate the prescription-to-administration time (PAT) for analgesia in patients presenting to the ED with pain and propose actionable recommendations for improvement. Methodology: This cross-sectional, non-interventional analytical study was conducted in the ED of a large teaching hospital on 300 patients, aged over 12 years with an initial pain score > 5. Pain scores and relevant time intervals were recorded and analyzed. Results: The mean PAT was 28 minutes. Of the total patients, 19% (n=58) received analgesia within 15 minutes, 66% (n=199) within 16-30 minutes, 13% (n=37) within 31-45 minutes, and 2% (n=6) within 46-60 minutes. Conclusion: The average PAT of 28 minutes aligns with existing literature. However, this can be further improved by implementing standardized pain assessment tools, clear documentation practices, and protocol-driven pain management strategies in the ED.